Sex-specific effects of peptidyl arginine deiminase 4 deficiency in the cafeteria diet-induced obesity-associated metabolic complications - Feješ, Andrej; Bečka, Emil; Feješ Slivková, Ivana; Macáková, Kristína; Šteňová, Emőke; Pastorek, Michal; Celec, Peter; Gardlík, Roman; Šebeková, Katarína; Borbélyová, Veronika (Frontiers in Endocrinology, 2026)
BackgroundObesity is a global health challenge linked to chronic non-communicable diseases. Low-grade inflammation and altered immune responses, including neutrophil extracellular trap (NET) formation, contribute to metabolic complications. Peptidyl arginine deiminase 4 (PAD4) is critical for NET formation, and its inhibition shows therapeutic potential. However, the sex-specific effects of PAD4 deficiency in diet-induced obesity remain unexplored.MethodsThis study investigated the impact of PAD4 deficiency on obesity-related metabolic pathologies in male and female C57BL/6 wild-type (WT) and Pad4(-/-) mice (n=5-6/group) fed a 22-week obesogenic cafeteria (CAF) diet. We hypothesized that PAD4 deficiency would ameliorate obesity-related metabolic and behavioral complications for both sexes. Body weight and composition, glucose and lipid metabolism, liver damage markers, and behavior were assessed. NETs were quantified via flow cytometry.ResultsPad4(-/-) males on CAF diet exhibited delayed obesity onset, lower body weight gain, and improved dyslipidemia than WT CAF males. This was associated with enhanced metabolic adaptation, indicated by higher brown adipose tissue temperature in Pad4(-/-) males. Conversely, Pad4(-/-) females on the CAF diet showed comparable weight gain to WT CAF females, similar or worsened dyslipidemia, impaired glucose metabolism, and higher liver lipid accumulation. While WT CAF females showed increased brown adipose tissue temperature, Pad4(-/-) CAF females did not.ConclusionPAD4 deficiency exerts sex-specific effects on obesity-related metabolic complications in mice. Inhibition of NET formation appears protective in males but not females on an obesogenic diet. These findings underscore the importance of considering sex as a biological variable in obesity research and developing sex-specific therapies.